2(u-1)=2u+2-2(-8u-1)

Since u is on the right side of the equation, switch the sides so it is on the left side of the equation.

2u+2-2(-8u-1)=2(u-1)

Simplify each term.

Apply the distributive property.

2u+2-2(-8u)-2⋅-1=2(u-1)

Multiply -8 by -2.

2u+2+16u-2⋅-1=2(u-1)

Multiply -2 by -1.

2u+2+16u+2=2(u-1)

2u+2+16u+2=2(u-1)

Simplify by adding terms.

Add 2u and 16u.

18u+2+2=2(u-1)

Add 2 and 2.

18u+4=2(u-1)

18u+4=2(u-1)

18u+4=2(u-1)

Apply the distributive property.

18u+4=2u+2⋅-1

Multiply 2 by -1.

18u+4=2u-2

18u+4=2u-2

Subtract 2u from both sides of the equation.

18u+4-2u=-2

Subtract 2u from 18u.

16u+4=-2

16u+4=-2

Subtract 4 from both sides of the equation.

16u=-2-4

Subtract 4 from -2.

16u=-6

16u=-6

Divide each term in 16u=-6 by 16.

16u16=-616

Cancel the common factor of 16.

Cancel the common factor.

16u16=-616

Divide u by 1.

u=-616

u=-616

Simplify -616.

Cancel the common factor of -6 and 16.

Factor 2 out of -6.

u=2(-3)16

Cancel the common factors.

Factor 2 out of 16.

u=2⋅-32⋅8

Cancel the common factor.

u=2⋅-32⋅8

Rewrite the expression.

u=-38

u=-38

u=-38

Move the negative in front of the fraction.

u=-38

u=-38

u=-38

The result can be shown in multiple forms.

Exact Form:

u=-38

Decimal Form:

u=-0.375

Solve for u 2(u-1)=2u+2-2(-8u-1)